EFEKTIVITAS PELAYANAN PEMUNGUTAN PAJAK KENDARAAN BERMOTOR MELALUI SAMSAT KELILING DI KOTA BATAM - Lena, Lena; Timbul Dompak (LPPM Universitas Putera Batam, 2022)
The efforts of the Regional Revenue Management Agency (BAPPENDA) in increasing motor vehicle tax revenues by providing Mobile Samsat services to make it easier for the community to make tax payments, especially people who live far from the Main Samsat. This is done with the aim of making people obedient in paying motor vehicle taxes. This study uses descriptive qualitative research to explain and provide an understanding of the effectiveness of motor vehicle tax collection services through the Mobile Samsat in the city of Batam. Sources of data used in this study are primary data and secondary data. The results of this study can be concluded that the effectiveness of motor vehicle tax collection services through the mobile samsat has been effective. However, there are still obstacles in the process of paying vehicle taxes, there are still complaints from taxpayers regarding the facilities and infrastructure, namely that there is no shelter that hinders the effectiveness of the Mobile Samsat service if the weather is rainy or hot. Then, the unstable internet network on the system used by Samsat Mobile, especially on rainy day. Keywords: Effectiveness; Taxes; Mobile Samsat.